Aksi Kamisan: Tantangan dan Kekuatan dalam Upaya Penuntasan Kasus HAM di Indonesia - Laras Ayu Andini; Miqdad Haqqony; Utami, Anisa (Wacana Publik, 2023)
The resolution of cases of human rights violations in Indonesia continues to meet a number of deadlocks. The community, the families and victims continue to hold the government accountable for not coming. Kamisan's action came as a response to the proliferation of unresolved cases. This action is dedicated to justice and commemorates the victims of human rights violations in a peaceful and symbolic way that stands still carrying a black umbrella in front of the state palace. The method used in this study is descriptive qualitative. Data is obtained through the involvement of various sources of information: interviews, observations, audiovisual materials, documents and various reports. The list of questions is organized using open-ended questions. Informants came from Kamisan Action Participants, families of victims, KontraS, and parties involved in Kamisan Action as the main actors in the kamisan action. The results of the data presented will provide an overview of how this action faces challenges as well as strength in efforts to reject the resolution of non-judicial human rights cases taken by the government. The results showed that Kamisan Action faced various challenges along the way. Legal obstruction, intimidation, political pressure and neglect from those who should be responsible. But on the other hand, this action has been a large public space. Forms of support flowed from the community with the emergence of similar actions in several cities in Indonesia. This action also raises awareness, preserves public memory and mobilizes the public to engage and fight against forgetting past sins that never lead to solutions and apologies.